2019
DOI: 10.1523/jneurosci.1250-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Differential Song Deficits after Lentivirus-Mediated Knockdown of FoxP1, FoxP2, or FoxP4 in Area X of Juvenile Zebra Finches

Abstract: Mutations in the transcription factors FOXP1 and FOXP2 are associated with speech impairments. FOXP1 is additionally linked to cognitive deficits, as is FOXP4. These FoxP proteins are highly conserved in vertebrates and expressed in comparable brain regions, including the striatum. In male zebra finches, experimental manipulation of FoxP2 in Area X, a striatal song nucleus essential for vocal production learning, affects song development, adult song production, dendritic spine density, and dopamine-regulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…VSV G-based transgenesis in finch compared to chicken and quail (12,14), two species with an intact LDLR. We also note that even in studies reporting behavioral effects from brain gene manipulations using VSV G LVs in finches, the number of infected cells is typically quite low (15)(16)(17).…”
Section: Resultsmentioning
confidence: 88%
“…VSV G-based transgenesis in finch compared to chicken and quail (12,14), two species with an intact LDLR. We also note that even in studies reporting behavioral effects from brain gene manipulations using VSV G LVs in finches, the number of infected cells is typically quite low (15)(16)(17).…”
Section: Resultsmentioning
confidence: 88%
“…The FoxP2 protein coding sequence is highly conserved between humans and songbirds as are the brain expression patterns, notably in the cerebellum and striatum [5][6][7] . Moreover, genetic manipulations of FoxP2 expression levels in the striatal song nucleus Area X during the critical phase of song learning lead to inaccurate and incomplete imitation of the tutor's song and more variable vocal production 3,[8][9][10] . This phenotype bears similarities to the specific speech deficits called developmental verbal dyspraxia, DVD (or childhood apraxia of speech), that patients carrying FOXP2 mutations suffer from.…”
Section: Dynamic Foxp2 Levels In Male Zebra Finches Are Linked To Mormentioning
confidence: 99%
“… 10 , 42 A recent study linking FoxP1/2/4 functions to vocal learning in songbirds suggested that FOXP4 should also be considered as a candidate for involvement in vocal disorders. 43 Indeed, all individuals with likely pathogenic FOXP4 variants in our study had delayed speech/language development, with expressive problems prominently present. As FOXP1, FOXP2, and FOXP4 show partially overlapping coexpression in various different regions of the developing brain, 10 further research is needed to delineate if loss-of-function of FOXP4 directly impairs speech/language development, or whether secondary disruption of FOXP1 and/or FOXP2 function via heterodimerization with dysfunctional FOXP4 could play a role as well.…”
Section: Discussionmentioning
confidence: 64%